2019
DOI: 10.1051/sicotj/2019038
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic research in low-income countries: A bibliometric analysis of the current literature

Abstract: Background: To perform a bibliometric analysis and quantify the amount of orthopaedic and trauma literature published from low-income countries (LICs).Methods and methods: The Web of Science database was utilised to identify all indexed orthopaedic journals. All articles published in the 76 orthopaedics journals over the last 10 years were reviewed, to determine their geographic origin.Results: A total of 131 454 articles were published across 76 orthopaedic journals over the last 10 years. Of these, 132 (0.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
6
16
0
Order By: Relevance
“…Most studies were reported from HICs which is similar to the general orthopaedic literature [72] . In this review only 2 studies were conducted in LMICs [ 26 , 42 ] and 48% of the studies were from the USA.…”
Section: Limitationssupporting
confidence: 56%
“…Most studies were reported from HICs which is similar to the general orthopaedic literature [72] . In this review only 2 studies were conducted in LMICs [ 26 , 42 ] and 48% of the studies were from the USA.…”
Section: Limitationssupporting
confidence: 56%
“…Our results show that a substantial proportion (more than 80%) of the existing research on post-discharge patients comes from high-income settings. This is in line with research on orthopedic trauma [ 43 ], fractures [ 44 ], and TBI [ 45 ] that similarly show low trauma research outputs from LMIC settings. This means that the current knowledge on post-discharge outcomes in trauma patients is largely based on evidence from high-income settings [ 46 – 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…Studies from MICs tended to score low in their methodological appraisal. This is comparable with other research on different sub-groups of trauma, such as orthopedic fractures and brain injuries, which shows that LMICs are under-represented in trauma research (100)(101)(102). Even the existing research from LMICs is represented by less than onefifth of the constituent countries (103).…”
Section: Discussionsupporting
confidence: 83%